Migration and inequalities around the Mediterranean Sea - Björn Nilsson; Racha Ramadan (Luxembourg Income Study (LIS), 2020)
This paper aims to quantify the effects from migration on net income distributions, disentangling the roles played by factor reallocation and remittances, and focusing on two (primarily) destination countries (Spain and Italy) and two (primarily) origin countries (Jordan and Iraq). Using LIS-ERF data sets for the four countries; the paper relies separately on a variant of a shift-share instrument to identify the effect of migration on inequalities at the regional level in Spain and Italy, and on quantile regression to estimate the impact of receiving remittances on per capita expenditure in Iraq and Jordan. The results suggest that migration increases inequality in both origin and receiving countries.
Keywords: D31; D63; O15; 330; Migration; income distribution; inequality; the Mediterrenean